The Dilemma of Corruption in a Decentralized System of Government - Hamidi, Abdul Basir (Journal of Governance, 2024)
While corruption may be found anywhere in the world, countries with weak institutions and unstable political environments tend to have more of it. Many countries have embraced decentralization as a workable solution for tackling corruption. The purpose of this study is to provide insight on how decentralization affects Indonesia's corruption problem. The research is qualitative library research, in which the data is collected from various sources such as journals from Scopus and Google Scholar, media reports, government documents, as well as books. The research indicates that local corruption has increased following decentralization, with local government officials, the private sector, and village heads being the most involved. The judiciary in Indonesia has a poor reputation due to low judicial standards, a dysfunctional criminal justice system, and lax enforcement, which have contributed to its poor reputation. By undertaking such research endeavors, the issues confronting corruption will be exposed, and the government of Indonesia will have a more comprehensive understanding of how to deal with corruption.